1997
DOI: 10.1128/cdli.4.4.400-404.1997
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblot reactivity of polyclonal and monoclonal antibodies with periplasmic flagellar proteins FlaA1 and FlaB of porcine Serpulina species

Abstract: The periplasmic-flagellum (PF) proteins of Triton X-100-soluble and Triton X-100-insoluble sodium dodecyl sulfate-treated fractions from reference and field strains of Serpulina hyodysenteriae, Serpulina innocens, and Serpulina pilosicoli were characterized by Western blotting with a rabbit polyclonal antibody (PAb) specific for the 44-kDa PF sheath protein of S. hyodysenteriae (Z. Li, F. Dumas, D. Dubreuil, and M. Jacques, J. Bacteriol. 175:8000-8007, 1993) and a murine monoclonal antibody (MAb), designated 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…However, flagellar proteins are highly conserved among spirochete species and genera, therefore false-positive results due to cross-reactivity are always a potential problem if these proteins are used for serologic tests (Jensen, 1997). This is consistent with polyclonal and monoclonal antibody reagents raised against B. hyodysenteriae cross-reacting with B. pilosicoli FlaA1 and FlaB by immunoblot (Fisher et al, 1997).…”
Section: Flagellar Proteinssupporting
confidence: 87%
“…However, flagellar proteins are highly conserved among spirochete species and genera, therefore false-positive results due to cross-reactivity are always a potential problem if these proteins are used for serologic tests (Jensen, 1997). This is consistent with polyclonal and monoclonal antibody reagents raised against B. hyodysenteriae cross-reacting with B. pilosicoli FlaA1 and FlaB by immunoblot (Fisher et al, 1997).…”
Section: Flagellar Proteinssupporting
confidence: 87%
“…Koopman and coworkers (24) and Li and coworkers (30) reported that PF protein FlaA1 has the greatest variability among the five PF proteins of intestinal spirochetes. We have shown that the PF FlaA1 protein is antigenically similar among porcine Serpulina species, as demonstrated by the immunoblot reactivity of an FlaA1-specific rabbit antiserum to the 44-kDa PF protein of intestinal spirochetes (13,30). However, Koopman and coworkers (24) suggested that there was polymorphism of the PF flaA1 gene among porcine S. hyodysenteriae isolates B204 and C5, S. innocens isolate B256, human B. aalborgi, and 24 nonclassified WBHIS isolated from humans (n ϭ 10), dogs (n ϭ 5), rats (n ϭ 4), mice (n ϭ 4), and a chicken.…”
Section: Discussionmentioning
confidence: 87%
“…Flagellar proteins are major immunoreactive proteins in B. hyodysenteriae (Kent et al, 1989 ). It has been reported that FlaA from S. hyodysenteriae, S. innocens , and S. pilosicoli was recognized by rabbit polyclonal and murine monoclonal antibodies produced against S. hyodysenteriae lysates (Fisher et al, 1997 ). However, no data were previously available on the antigenicity of B. pilosicoli FlaA.…”
Section: Discussionmentioning
confidence: 99%